The crack in the lens [compact disc, unabridged] - Hockensmith, Steve (Hockensmith, Steve. Holmes on the range., 2009)
Otto "Big Red" and his brother Gustav "Old Red" head to San Marcos to deal with the greatest tragedy of Old Red's life. His fiancée, a fallen woman at the local house of ill repute, was murdered and the case was swept under the rug by the local authorities. Old Red is determined to find out what really happened and to find justice for his beloved. But Big Red and Old Red find themselves facing a wall of silence and in some of the worst situations of their lives.